MODEL PENGUKURAN HUBUNGAN KEBISINGAN DENGAN STRES KERJA DAN TINGKATAN STRES PADA KARYAWAN - Eddi Indro Asmoro; Gilang Rachmat Pratama (Jurnal Ilmiah Dinamika Teknik, 2018)
Occupational Health and Safety (OHS) is the company's social responsibility and obligations to employees for the guarantee of industrial assets. One physical factor that can be understood and understood is what is asked. Confusion caused by stress on someone who is exposed to an appointment. This study is to make a model for measuring the relationship between work stress and levels stress on the employees of tablets and tablets saluted by PT. Erlimpex Semarang. The type of this research is observational analytic with all the research of all tablets and tablets saluting PT. Erlimpex Semarang. The instrument in this study is an analysis of the assessment of the expectations issued to employees. Data analysis in this study was conducted using doubles linear regression analysis for making a measurement model an influence and levels of influence. Based on the results of the analysis of this study, it is expected that the calculation model in calculation representative. "There is a relationship between work stress on the labor of tablets and tablets salute PT. Erlimpex Semarang ", which was obtained using a doubles linear regression test measurement model. Keywords: Measurement Model, Variable Indicator, Confusion, Job Stress,Levels of Influence, Work Circle